Effects of alteplase for acute stroke according to criteria defining the European Union and United States marketing authorizations: Individual-patient-data meta-analysis of randomized trials. Issue 2 (February 2018) - Hacke, Werner; Lyden, Patrick; Emberson, Jonathan; Baigent, Colin; Blackwell, Lisa; Albers, Gregory; Bluhmki, Erich; Brott, Thomas; Cohen, Geoffrey; Davis, Stephen M; Donnan, Geoffrey A; Grotta, James C; et al.
Background: The recommended maximum age and time window for intravenous alteplase treatment of acute ischemic stroke differs between the Europe Union and United States. Aims: We compared the effects of alteplase in cohorts defined by the current Europe Union or United States marketing approval labels, and by hypothetical revisions of the labels that would remove the Europe Union upper age limit or extend the United States treatment time window to 4.5 h. Methods: We assessed outcomes in an individual-patient-data meta-analysis of eight randomized trials of intravenous alteplase (0.9 mg/kg) versus control for acute ischemic stroke. Outcomes included: excellent outcome (modified Rankin score 0–1) at 3–6 months, the distribution of modified Rankin score, symptomatic intracerebral hemorrhage, and 90-day mortality. Results: Alteplase increased the odds of modified Rankin score 0–1 among 2449/6136 (40%) patients who met the current European Union label and 3491 (57%) patients who met the age-revised label (odds ratio 1.42, 95% CI 1.21−1.68 and 1.43, 1.23−1.65, respectively), but not in those outside the age-revised label (1.06, 0.90−1.26). By 90 days, there was no increased mortality in the current and age-revised cohorts (hazard ratios 0.98, 95% CI 0.76−1.25 and 1.01, 0.86–1.19, respectively) but mortality remained higher outside the age-revised label (1.19, 0.99–1.42). Similarly, alteplase increased the odds of modified Rankin score 0-1 among 1174/6136 (19%) patients who met the current US approval and 3326 (54%) who met a 4.5-h revised approval (odds ratio 1.55, 1.19−2.01 and 1.37, 1.17−1.59, respectively), but not for those outside the 4.5-h revised approval (1.14, 0.97−1.34). By 90 days, no increased mortality remained for the current and 4.5-h revised label cohorts (hazard ratios 0.99, 0.77−1.26 and 1.02, 0.87–1.20, respectively) but mortality remained higher outside the 4.5-h revised approval (1.17, 0.98–1.41). Conclusions: An age-revised European Union label or 4.5-h-revised United States label would each increase the number of patients deriving net benefit from alteplase by 90 days after acute ischemic stroke, without excess mortality.